Use of monoclonal antibodies to identify serotypes of enterovirus isolates - Rigonan, A S; Mann, L; Chonmaitree, T (Journal of clinical microbiology, 1998)
Nonpoliovirus enteroviruses cause a variety of diseases that are common in young children and adults. The "gold standard" for laboratory diagnosis of enteroviruses is cell culture isolation, followed by serotype identification by neutralization assay. These procedures are time-consuming and expensive. Rapid serotype identification of enteroviruses is important in differentiating nonpoliovirus enterovirus pathogens from vaccine strain polioviruses that can be shed for some time after vaccination. In the present investigation, we evaluated a rapid method for serotype identification of enteroviruses by indirect immunofluorescence assay (IFA) using commercially available monoclonal antibodies for polioviruses, coxsackieviruses type B, and six serotypes of commonly circulating echoviruses. Of 291 isolates of enteroviruses included in the study, 95 were polioviruses and 196 were nonpoliovirus enteroviruses. Two hundred thirty-four of these (38 polioviruses and 196 nonpoliovirus enteroviruses) were consecutively grown in the laboratory over a 5-year period. IFA identified the serotypes of 74% of the consecutive isolates and 71% of all enterovirus isolates by yielding a positive staining result. The levels of agreement in the identification of the enterovirus group between IFA and neutralization tests were 92% for consecutively grown isolates and 85% for all enterovirus isolates. The sensitivity of the IFA for the detection of viruses for which specific monoclonal antibodies were applied was 73% for polioviruses, 85% for coxsackieviruses type B, and 94% for echoviruses. Specificity was near 100% for polioviruses and coxsackieviruses type B and 94% for echoviruses. We conclude that IFA can be helpful as a preliminary test for serotype identification of enteroviruses. The results are most accurate when the test identifies the isolate as a poliovirus.